Longitudinal recovery trajectories and ventilatory modalities in COVID-19 acute respiratory distress syndrome survivors - Jessica González; Iván D. Benítez; Sally Santisteve; Anna Vila; Maria Aguilà; Gerard Torres; Anna Sánchez-Cucó; Mar Malla-Bañeres; Anna Moncusí-Moix; Jordi de Batlle; Esther Gracia-Lavedan; Adrián Ceccato; et al. (ERJ Open Research)
Background The impact of different ventilatory support modalities and timing of intubation on longitudinal lung recovery trajectories in patients with severe coronavirus disease 2019 (COVID-19) is unknown. Methods This was a multicentre, prospective observational study conducted in 52 Spanish intensive care units (ICUs) involving critically ill COVID-19 patients admitted between 25 February 2020 and 8 February 2021. 1854 COVID-19 patients were followed after hospital discharge at 3, 6 and 12 months with diffusing capacity of the lung for carbon monoxide (DLCO) measurements and chest imaging. Patients were classified regarding the ventilatory support received during the ICU stay: noninvasive mechanical ventilation (NIMV), high-flow nasal cannula (HFNC) and invasive mechanical ventilation (IMV), divided into early IMV (intubation within 24 h) and late IMV (intubation after 24 h). The primary objective was to evaluate the impact of the different respiratory support modalities during the ICU stay and the time of intubation on DLCO measurements and their recovery trajectories over a 1-year follow-up. Secondary outcomes included other pulmonary function parameters and chest imaging findings. Results A total of 360 (19.4%) and 290 (15.6%) patients received HFNC and NIMV, respectively. 1204 (64.9%) patients underwent IMV; 966 received early IMV and 238 received late IMV. The latter exhibited a significantly worse percentage predicted DLCO during the 1-year follow-up with adjusted differences of 6.9 (95% CI 3.9–10; p<0.001), 4.2 (95% CI 1.1–7.2; p=0.007) and 4.9 (95% CI 1.7–8.2; p=0.003) at 3, 6 and 12 months compared with early IMV. NIMV patients exhibited greater lung damage at follow-up than those under HFNC with an adjusted difference of percentage predicted DLCO of 5.2 (95% CI 1.7–8.7; p=0.003) at 6 months and greater presence of radiological abnormalities during follow-up. Matched and sensitivity analysis showed results consistent with those reported. Conclusions Delay in intubation implies the worst outcomes; however, patients with NIMV exhibited a slower lung recovery in terms of DLCO measurements and more radiological abnormalities compared with HFNC patients. These results should be used to optimise follow-up protocols for COVID-19 acute respiratory distress syndrome (ARDS) survivors.